A pragmatic approach towards healthcare needs in Malaysia through student-led dietetics clinic - Yew, Yang Wai; Swee, Winnie Chee Siew; Arasu, Kanimolli; Ambrose, Charmaine Alphonso Augustin; Samingan, Nur Adila; Sahathevan, Sharmela; Xuan, Wong Ting; Qian, Yap Zi (Asian Federation of Dietetics Association, 2024)
Background and purpose While the concept of student-led clinics is well-established, the available evidence has been limited to multidisciplinary teams, and in North America. There is a notable gap in researching and implementing this model within dietetics, especially in resource-scarce and high disease-burden developing countries. Methods. The student-led dietetics clinic began with the formation of a project management team, a 2-tier team in December 2022. The implementation of SDC was carefully considered by multiple factors including operation, finance, and public outreach. The academic team consist of faculty members providing guidance and oversight on the setting up and operations of the clinic to meet students' learning outcomes. The students’ team planned the daily operations of the clinic and developed resources for its operations including rotation of students on duty to manage the clinic, and strategies to obtain referrals for the clinic. Result. The student-led dietetics clinic presents valuable opportunities for early clinical exposure, leadership development, interprofessional skills, and practising empathy. Its accessibility to address underserved community needs should be explored more effectively. Conclusion. Therefore, this pragmatic approach not only benefits the student dietitians’ professional development but contributes to the overall improvement of public health through specialised dietary services.